The Economic Calculus of AI in Medicine: Is Artificial Intelligence Reducing Physician Salaries? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The rapid integration of Artificial Intelligence AI into the healthcare ecosystem has sparked a critical and often anxious debate: is this technological leap...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care